Multidrug-Resistant Pseudomonas aeruginosa Accelerate Intestinal, Extra-Intestinal, and Systemic Inflammatory Responses in Human Microbiota-Associated Mice With Subacute Ileitis - Heimesaat, Markus M.; Escher, Ulrike; Grunau, Anne; Kühl, Anja A.; Bereswill, Stefan (Frontiers in Immunology, 2019)
The globally rising incidences of multidrug-resistant (MDR) Pseudomonas aeruginosa (Psae) in humans and live-stock animals has prompted the World Health Organization to rate MDR Psae as serious threat for human health. Only little is known, however, regarding factors facilitating gastrointestinal Psae-acquisition by the vertebrate host and subsequently induced inflammatory sequelae. In the present study, we addressed whether subacute ileitis predisposed mice harboring a human gut microbiota for intestinal MDR Psae carriage and whether inflammatory responses might be induced following peroral challenge with the opportunistic pathogen. To accomplish this, secondary abiotic mice were associated with a human gut microbiota by fecal microbiota transplantation. Ten days later (i.e. on day 0), subacute ileitis was induced in human microbiota associated (hma) mice by peroral low-dose Toxoplasma gondii infection. On day 5 post-infection, mice were perorally challenged with 109 colony forming units of a clinical MDR Psae isolate by gavage and the fecal bacterial loads surveyed thereafter. Four days post peroral challenge, only approximately one third of mice with a human gut microbiota and subacute ileitis harbored the opportunistic pathogen in the intestinal tract. Notably, the gut microbiota composition was virtually unaffected by the Psae-carriage status during subacute ileitis of hma mice. The Psae challenge resulted, however, in more pronounced intestinal epithelial apoptotic cell and T-lymphocyte responses upon ileitis induction that were not restricted to the ileum, but also affected the large intestines. Higher Psae-induced abundances of T-cells could additionally be observed in extra-intestinal compartments including liver, kidney, lung, and heart of hma mice with subacute ileitis. Furthermore, higher apoptotic cell numbers, but lower anti-inflammatory IL-10 concentrations were assessed in the liver of Psae as compared to mock treated mice with ileitis. Remarkably, Psae-challenge was accompanied by even more pronounced systemic secretion of pro-inflammatory cytokines such as TNF and IL-6 at day 9 post ileitis induction. In conclusion, whereas in one third of hma mice with subacute ileitis Psae could be isolated from the intestines upon peroral challenge, the opportunistic pathogen was responsible for inflammatory sequelae in intestinal, extra-intestinal and even systemic compartments and thus worsened subacute ileitis outcome irrespective of the Psae-carrier status.